Hepatoprotective Effects of Balinese Grape Extract (Vitis vinifera L.) on Hepar Histology and Reducing Blood Sugar Levels - Damayanti, Ida Ayu Manik; Wicaksana, I Gusti Agung Tresna; Sutrisna, I Putu Gede (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study aimed to determine the hepatoprotective activity of grape skin extract (Vitis vinifera L.) (BGE) on hepatic histology and blood sugar level reduction. This study was conducted in four stages: extraction of grape skin using 96% ethanol, phytochemical screening, antihyperglycemic activity test and hepatoprotective activity test. The experimental animals were divided into five groups consisting of negative control (Na CMC 0.5%), positive control (Curcuma), TI (100 mg BGE/kg BW), TII (300 mg BGE/kg BW), TIII (500 mg BGE/kg BW). Phytochemical screening showed that BGE positively contains terpenoids, flavonoids, tannins, saponins and carotenoids. The results of antioxidant analysis on BGE showed an IC50 value of 80.77 ppm, which included intense antioxidant activity. BGE and negative control can provide hepatoprotector effects on hepatic cells from hepatocyte cell damage due to paracetamol and can reduce blood sugar levels.